Factors Contributing to the Success of the Saving Group for Production, with Results very satisfactory. In Chondaen District, Phetchabun Province - Khunyotha , Ritthichai; wongwatthanaphong, kampanart (Journal of Modern Learning Development, 2021)
Objective of this research: 1. To study the factors affecting the success of the production savings group with good performance 2. To study the relationship between the factors affecting the success of the savings group for the production of good performance. Production and success of the savings for production with good performance and 3. To study problems, obstacles and recommendations for the operations of the savings for production with good performance in the area of ​​Chon Daen District. Phetchabun Province It is a quantitative research. With members and committees of the Savings for Production Group with good performance in the area of ​​Chon Daen District Phetchabun Province: 244 people from the representation in the formula of Taro Yanmane using questionnaires as a research tool. The data were analyzed using frequency distribution, mean, standard deviation, percentage, and multiple regression analysis. The research findings were as follows: 1. The five factors affecting the success of the savings group were at a high level. 2. The relationship between factors affecting the success of the savings for production group and the success of the group. Savings for production with good performance found that the member’s perception factor (Beta = 0.476), the leadership factor of the board (Beta = 0.385), the cognitive factor in the roles and duties of the committee. (Beta = 0.159) and government support factors (Beta = 0.138), respectively, positively affect the success of the production savings group with good performance. At the level of 0.05, the relationship could be forecast 88.6% (R2 = .886). It was found that some members were unable to make payments on the borrowings within the specified period of time, the committee lacked effective database or other information. And the members did not really participate in expressing opinions.